The Writing Culture of Scholars of The Aceh kingdom - Adrian Rahmadani (Winaya Inspirasi Nusantara Foundation, 2024)
The writing practices of scholars under the Aceh monarchy are examined in this scientific essay. Scholars from throughout the Muslim world and the archipelago flocked to Aceh, which developed into a center of learning and played a vital role in developing intellectual traditions. The official language of Malay's adoption had a profound effect on political, intellectual, and economic discourses. Numerous publications were written by Islamic scholars, or ulama, and Islamic discourse flourished in mosques, schools, and the royal palace, demonstrating the royalty's support of education. Aceh made a significant cultural and Islamic contribution to the growth of Malay literature and language. Awareness Aceh's past intellectual traditions requires an understanding of the written culture of the area.